Constraints on a scalar-pseudoscalar Higgs mixing at future e +e- colliders: An update - Chalov, A.; Likhoded, A.; Rosenfeld, R. [UNESP] (American Physical Society (APS), 2004)
We perform an update of our previous analysis of the constraints on possible deviations of Hbb̄ coupling parametrized as (mb/ν) (a+iγ5b), arising from a scalar-pseudoscalar mixing, where the process e+e- →bb̄νν was used. In this paper we include a complete simulation of the process e+e -→+bb̄e+e- and combine these results to obtain tighter bounds on the deviations of the parameters a and b from their standard model values that could be measured at the Next Linear Collider.